The Construction of Womanhood and the Commodification of Identity - Manoussaki, Kallia; Hayne, Ann; Donaldson, Anni (Advances in Social Sciences Research Journal, 2026)
This paper argues that the role of the female body in the experience of womanhood, is key to the worldwide epidemic of violence against women and central to the ongoing transgender debate. We argue that within current ideological discussion of gender fluidity, the female biology has been deemed inconsequential, secondary to womanhood whilst also remaining the primary cause of violence towards natal females. We further argue that womanhood is socially constructed, based largely on men’s perceptions of women’s biological bodies, which has historically framed the experiences of women, shaping their perceived inferiority. The physical body informed the performance of womanhood, and its physical presentation was at the centre of the battle for equality. Whilst supporting rights of those who want to transition to live free from discrimination, we argue for the need to look at current transgender debates in the context of increased commodification of women’s bodies, women’s bodies as sites of make violence, and be cognisant of the role that the female body has played in the experience of womanhood, collective fear of the male form and the need to seek safety from it.